1990
DOI: 10.2307/526298
|View full text |Cite
|
Sign up to set email alerts
|

Severn Valley Wares: A Reassessment

Abstract: Severn Valley Ware has long been recognized as one of the most widespread and enduring classes of Roman coarse pottery found on sites in the west of England. It is usually represented in a distinctive orange, or less commonly, light grey-coloured fabric in a characteristic range of forms including jars, tankards and bowls. A detailed distribution of these wares on a national scale has never been compiled, although it is known that Severn Valley Wares have been found in greater or lesser quantities from Somerse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Strong similarities can be found in the ceramic handled tankards of Durotrigan and Severn Valley Wares (see Brailsford 1958, 103, figs 1, 8; Webster 1976, 30–1, Class E; Timby 1990, 251). Examples of the former are found exclusively within the conventional zone of the Durotriges (primarily Dorset and its borders) and have been noted at Hod Hill and accompanying burials at Jordan Hill and Maiden Castle (Wheeler 1943, 233; Brailsford 1958, 118–9; Richmond 1968, 37, fig.…”
Section: Parallels Within Iron Age Materials Culturementioning
confidence: 96%
See 1 more Smart Citation
“…Strong similarities can be found in the ceramic handled tankards of Durotrigan and Severn Valley Wares (see Brailsford 1958, 103, figs 1, 8; Webster 1976, 30–1, Class E; Timby 1990, 251). Examples of the former are found exclusively within the conventional zone of the Durotriges (primarily Dorset and its borders) and have been noted at Hod Hill and accompanying burials at Jordan Hill and Maiden Castle (Wheeler 1943, 233; Brailsford 1958, 118–9; Richmond 1968, 37, fig.…”
Section: Parallels Within Iron Age Materials Culturementioning
confidence: 96%
“…Severn Valley Ware tankards appear in the post-conquest period and take their inspiration from Durotrigan types (Webster 1977; Timby 1990, 249–51). They are predominantly distributed throughout the Severn basin, though a considerable number of examples are found further afield in the west Midlands, Welsh Marches, and in northern Britain, reaching as far north as the Antonine Wall in the mid- to late-2nd century ad (Webster 1977, 172).…”
Section: Parallels Within Iron Age Materials Culturementioning
confidence: 99%
“…Booth and Willis 1997, 53). Timby has suggested that the tradition appears shortly before the Roman conquest (Timby 1990). The present writer finds no reason to question this hypothesis and so an approximate date of c. AD 30 for the debut of the pottery of this tradition is proposed here as a heuristic solution.…”
Section: Oxidized Fabricsmentioning
confidence: 99%
“…However, these wares do not achieve the prominence of Oxfordshire red/brown colour-coated ware during the late Roman period. Examples of the latter fine ware have been (Webster 1976;Timby 1990). In sum the picture verifies a modest level of fine ware use at the site, with samian and then, to a lesser degree Oxfordshire red/brown colour-coats, the main fine ware types present.…”
Section: Functional Types Fine Wares and Pottery Functionmentioning
confidence: 99%
“…However, the source of the tiles could represent a choice between military and civilian supply, with the selection of a civilian supplier emphasising the pre-Roman regional political or social networks. Given the Iron Age origins of Severn Valley Ware (Timby 1990), these connections probably pre-date the Roman invasion, when the nearby hillfort at Credenhill was occupied (Wilmott and Rahtz 1985: 119). Nevertheless, the occurrence of SEDBBl, the distribution of which has been linked to the military, specifically Legio II Augusta, by Fulford (Allen and Fulford 1996;Fulford 1996), and the military metalwork mentioned above also suggest links to the military.…”
Section: An Interpretative Example: Kenchestermentioning
confidence: 99%